Implementation of The Project to Strengthen Pancasila Student Profiles at Muhammadiyah Vocational School - Jatmoko, Dwi; Isbakhi, Ari Fajar; RohmanRohman, Fikri Nur; Basuki, Basuki; Purwanto, Joko; Nurhidayati, Nurhidayati (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to determine the implementation process of the Strengthening Pancasila Student Profile (P5) Project at SMK Muhammadiyah Sampang. The method used is a descriptive method. The data analysis technique uses qualitative data analysis techniques. Data collection uses interview, observation and documentation data collection techniques. From the results of the research that has been carried out, it can be concluded that the stages of implementing P5 at SMK Muhammadiyah Sampang start from introducing P5 to the school community, preparing the school ecosystem then project design starting from designing time, allocation dimensions and Pancasila student profiles, forming a project facilitation team, identifying school readiness , selecting themes, determining topics, designing project modules and implementing work degrees. The biggest obstacle faced by SMK Muhammadiyah Sampang regarding P5 is related to teachers' limited understanding of P5. Some of the obstacles in presentations are also the same, namely the large amount of additional equipment in the learning process and job titles that require additional costs, there are students who are less enthusiastic, and differences in student abilities. The solution to overcome this is by making good use of existing facilities, improving the quality of learning, increasing students' understanding abilities, establishing communication with parents and completing facilities and infrastructure.